The Future Of The Indigenous Languages Of Kenya And Tanzania - Kioko, Angelina Nduku; Rugemalira, Josephat (My University, 2022)
This paper examines the language policies and practices in Kenya and Tanzania and argues that, in spite of the observable differences between these neighbouring countries, the ethnic community languages face an uncertain future. Although language policies play a role in determining this future, there are stronger forces that defy language policy, viz. population movements, urbanization, technological changes affecting mass communication, and the structure of the economies.
Keywords: Language policies; SOCIAL SCIENCES::Other social sciences::Mass communication; Indigenous languages